2012
DOI: 10.1111/cid.12013
|View full text |Cite
|
Sign up to set email alerts
|

Crestal Bone Loss and Oral Implants

Abstract: The summed frequency of peri-implantitis and implant failure is commonly less than 5% over 10 years of follow-up for modern implants when using established protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(201 citation statements)
references
References 28 publications
8
185
1
7
Order By: Relevance
“…This could be attributable to a theoretical response to device installation (Albrektsson et al. 2012) with re‐establishment of the biological width and maturation of the barrier function that takes place following bacterial invasion of the implant/abutment interface and requires 6–8 weeks of healing (Canullo et al. 2012, Hermann et al.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributable to a theoretical response to device installation (Albrektsson et al. 2012) with re‐establishment of the biological width and maturation of the barrier function that takes place following bacterial invasion of the implant/abutment interface and requires 6–8 weeks of healing (Canullo et al. 2012, Hermann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mombelli, Muller and Cionca (2012) calculated the prevalence of peri‐implantitis, based on 29 papers, in the order of 10% of the affected implants and 20% patients during 5–10 years after implant placement. Another review summarizing 10 papers reporting on the 10‐year clinical outcome with implants treated by sandblasting, grit blasting, acid‐etching, or combined treatments revealed that the survival was above 95% and <5% were diagnosed with purulent infection or peri‐implantitis (Albrektsson, Buser & Sennerby, 2012). A 10‐year follow‐up study including nearly 300 implants in 100 subjects revealed similar figures (Cecchinato, Parpaiola & Lindhe, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations, such as the ones above described have led to significant controversies among researchers regarding the rather alarming figures currently reported in peri-implantitis prevalence. In 2012, Albrektsson et al 3 concluded that, under established protocols, periimplantitis prevalence figures were under 5% for modern implants, and suggested caution in the interpretation of data in order to avoid an undesirable over-estimation on the prevalence of peri-implant disease, as results on periimplantitis prevalence studies can be heavily influenced by substantial methodological limitations. However, Atieh et al 10 verified in a recent systematic review that the summary estimates for the frequency of peri-implantitis were 18.8% of participants and 9.6% of implants.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implantitis was defined at the Consensus meeting on Peri-implantitis 3 as an 'infection with suppuration associated with clinically significant progressing marginal bone loss after the adaptive phase, usually restricted to the first year of function'. According to the American Academy of Periodontology, 4 peri-implantitis is 'an inflammatory process around an implant that includes both soft tissue inflammation and loss of supporting bone'.…”
Section: Definition and Prevalencementioning
confidence: 99%